Geographies of energy transition: the case of high-performing commercial office space in the central business districts of Sydney and Melbourne, Australia. Issue 1 (2nd January 2019) - Carr, Chantel; McGuirk, Pauline; Dowling, Robyn
ABSTRACT: As a signatory to the Paris Climate Agreement, Australia committed to reduce emissions significantly by 2030. In a country highly urbanised and dependent on fossil fuels as its primary energy source, one key avenue for meeting these commitments is energy transition in the built environment. Australia has emerged as a leader in the design and construction of high-performance buildings in the premium commercial office sector. In this paper, we address a significant gap in understanding the diverse mechanisms through which building energy transition is being constituted in this sector, focusing on Sydney and Melbourne. In the absence of substantive publicly available data, we draw on mixed methods comprising a database developed around high-performing CBD office buildings and qualitative interviews with a range of sectoral stakeholders. We characterise the building stock in each city, and document five trends constituting energy transitions. We demonstrate that building energy transitions are not only shaped purposefully by dominant governance regimes but also by opportunistic responses to specific material and commercial conditions and legacies in each city. Thus the urban built environment affords significant opportunity for energy transitions, but pathways towards such transitions are necessarily multiple and ultimately shaped by material as well as institutional geographies.